Effect of stem borer Eldana saccharina (Lepidoptera: Pyralidae) on the yield of maize - Bosque Pérez, N.A.; Mareck, J.H. (Cambridge University Press, 1991)
Field experiments were conducted in the dry season of 1985–86 and the first and second rainy seasons of 1986 at Ibadan, Nigeria, to assess the level of damage and yield reductions caused by Eldana saccharina Walker to maize. Grain weight per plant in artificially infested plots was up to 36% lower than grain weight per plant in insecticide-protected plots. Artificially infested plots had significantly lower 100-grain weight than insecticide-protected ones. The regression coefficient obtained from covariance analysis revealed that 100-grain weight decreased by 0.125 g for each unit increase in the percentage of the stem tunnelled. Infestations of E. saccharina were found to increase significantly the incidence and severity of stalk rots. Mutsaers, H.J.W. & Walker, P. (1991). On-Farm research in theory and practice: Proceedings of a workshop on design and analysis of on-farm trials, 27 February- 3 March 1989, Ibadan, IITA.